Relationship between feed efficiency and reproductive measurements in beef cattle. - Blair, Erika Elaine (Kansas State University, 2011)
It is important for animals to be feed efficient and reproductively sound to optimize profits for cow- calf producers. The objective of this study was to determine the relationship between feed efficiency and reproductive performance. Feed efficiency measures included residual feed intake (RFI), feed to gain ratio (F:G) and daily dry matter intake (DMI). Reproductive measurements were pregnancy rate, first service conception rate, pregnancy type (AI, natural. open), calving percentage, calving day (CD) and age at first calving. Two data sets which included 136 crossbred Angus females sired by bulls with high or low RFI estimated breeding values (EBV) with multiple parity information and 56 purebred Hereford heifers with their first parity calving information were analyzed. Initially, the crossbred Angus females were analyzed based on their phenotypic RFI values. There was no difference in pregnancy rate between the feed efficiency measures. Second parity pregnant females had lower (F:G) with first service conception (P=0.053), and pregnancy types (P=0.014) than the open (less efficient) females. In parity 5, phenotypically efficient RFI Angus females were pregnant to first service conception versus inefficient RFI Angus females (P=0.052) and those with lower DMI were diagnosed pregnant (P=0.0002). When evaluated as a repeated trait, RFI was not a significant indicator of CD (P=0.514). Crossbred Angus females were analyzed based on their sire’s RFI EBV and grouped accordingly into high (inefficient) or low (efficient) RFI sires. Females sired by high or low RFI (EBV) bulls showed no difference for the reproductive traits, except for a tendency for inefficient sired heifers to have a lower calving percentage in parity 2 (P=0.048). When CD was analyzed as a repeated measure, no difference between sire groups was found (efficient CD of 35.64 d, inefficient CD of 34.23, p = 0.789). In the Hereford heifers, RFI was not an indicator of CD (P = 0.774). There was also no difference in RFI between pregnant and open Hereford females with pregnant females having an LSMean of 0.11 kg/d and the open females having an LSMean of 0.14 kg/d (P = 0.860). Further research needs to be done to confirm any relationships between feed efficiency and reproduction.
Keywords: Feed Efficiency; Reproduction; Residual Feed Intake; Animal Sciences (0475); Genetics (0369)